Penerapan Strategi Pembelajaran Reading Guide dengan Media Lembar Kerja Siswa (LKS) untuk Meningkatkan Hasil Belajar Biologi Siswa Kelas VII SMP Tunas Bangsa Makassar - Astuti, Wiwik Wiji (Biology Teaching and Learning, 2020)
Abstract. This research is a classroom action research which aims to improve the learning outcomes of seventh grade students of SMP Tunas Bangsa Makassar through the use of the Reading Guide Learning Strategy with Student Worksheet Media (LKS). The subjects of this study were the seventh-grade students of SMP Tunas Bangsa Makassar which consisted of 26 students. Data collection techniques include learning activity data obtained through observation sheets and student biology learning outcomes data obtained using student biology learning outcomes tests which are then analyzed using descriptive statistics. The results of observations of student learning activities show that in general there has been an increase from cycle I to cycle II in each observed student learning activity. The results of quantitative descriptive statistical analysis of students' biology learning outcomes showed that the average student learning outcomes in the first cycle was 75,19 and in the second cycle was 79,23 so that the percentage increase in student biology learning outcomes is obtained by 4,04.Â Keywords:Â Reading Guide, LKS and Learning Outcomes